The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1038/sj.gt.3300819
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral injection of oligonucleotides to the NFκB binding site inhibits cachexia in a mouse tumor model

Abstract: Cancer cachexia, characterized by anorexia, weight loss muscle mass and food intake, which were induced by the and progressive tissue wasting, has been postulated to be tumor presence. Interleukin 6 mRNA in the tumor was also mediated by various cytokines. However, the precise markedly decreased by the transfection of NF B decoy mechanism of cachexia induction is not fully explained. We ODN. It is known that the transcriptional factor E2F plays have developed synthetic double-stranded oligodeoxynua pivotal rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
69
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(74 citation statements)
references
References 34 publications
2
69
1
2
Order By: Relevance
“…transcription factor. [11][12][13][14][15]30 Synthetic ODN were washed with 70% ethanol, dried and dissolved in sterile Tris-EDTA buffer (10 mM Tris, 1 mM EDTA). The supernatant was purified over a NAP 10 column (Pharmacia, Uppsala, Sweden), and quantitated by spectrophotometry.…”
Section: Figure 9 Limited Inhibitory Effects Of Nf-kb Decoy Odn On Skmentioning
confidence: 99%
See 1 more Smart Citation
“…transcription factor. [11][12][13][14][15]30 Synthetic ODN were washed with 70% ethanol, dried and dissolved in sterile Tris-EDTA buffer (10 mM Tris, 1 mM EDTA). The supernatant was purified over a NAP 10 column (Pharmacia, Uppsala, Sweden), and quantitated by spectrophotometry.…”
Section: Figure 9 Limited Inhibitory Effects Of Nf-kb Decoy Odn On Skmentioning
confidence: 99%
“…9,10 Therefore, the decoy approach enables us to treat diseases by modulating endogenous transcriptional regulation. [11][12][13][14][15] We hypothesized that the skin's allergic response in atopic dermatitis might be improved by the transfection of NF-kB decoy ODN. If the expression of cytokines and adhesion molecules involved in the development of atopic skin conditions, the most important step in the process of atopic dermatitis might be suppressed by NF-kB decoy ODN in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The NF-kB decoy ODN strategy has been applied to various diseases, such as re-stenosis after angioplasty or stenting, glomerulonephritis, rheumatoid arthritis and atopic dermatitis (see review 19 ). In oncology, it has been reported that the intra-tumor injection of NF-kB decoy ODN inhibited the cachexia induced by adenocarcinoma 20 and that intravenous treatment with NF-kB decoy ODN inhibited the hepatic metastasis of M5076 reticulosarcoma in mice. 21 Therefore, we hypothesized that transfection with NF-B decoy ODN would suppress the tumor growth and pulmonary metastases of osteosarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…29 The decoy strategy has recently been developed 30 and is considered a useful tool for analyzing the blockade of the expression of a wide variety of NF-B-dependent proinflammatory mediators. 31,32 Recent evidence has demonstrated that synthetic double stranded ODN as decoy cis elements block the binding of NF-B to promoter regions of its targeted genes, resulting in the inhibition of gene transactivation in vitro [33][34][35] and in vivo. 31,32 An alternative approach utilizes a cell-permeable peptide, called SN-50, carrying a functional domain NLS capable of inhibiting the nuclear translocation of NF-B complexes.…”
Section: Introductionmentioning
confidence: 99%